Youth aspirations and the reality of jobs in Africa - Lorenceau, Adrien (OECD Publishing, 2021)
The gap between youth aspirations and the reality of the labour markets in Africa is large. Career aspirations of young Africans have little in common with current and projected labour demand in the region, making it unlikely that they will go through a smooth school to work transition. Evidence from ten African countries shows that what youth in these countries value most is job security, such as work in the public sector. Agriculture-related work or medium-skilled jobs in manufacturing are the least attractive for young Africans. Policies can help address the misalignment between youth employment preferences and employment opportunities. A two-pronged approach is recommended: i) helping young people shape career aspirations that are realistic and that can fit with the world they will be entering, and ii) improving the quality of jobs with due regard to the job conditions that matter for young people
Keywords: Development